A Cross-Sectional Seroepidemiological Study on Infectious Bursal Disease in Backyard Chickens in the Mymensingh District of Bangladesh. (20th July 2022) - Mili, Sharmin Akhter; Islam, Md. Saiful; Al Momen Sabuj, Abdullah; Haque, Zobayda Farzana; Pondit, Amrita; Hossain, Md. Golzar; Hassan, Jayedul; Saha, Sukumar
Abstract : Infectious bursal disease (IBD) is a highly contagious disease that causes significant economic loss in chickens. A cross-sectional study was conducted in the Mymensingh district of Bangladesh to determine the seroprevalence of IBD virus (IBDV) antibodies in backyard chickens and their association with different epidemiological risk factors. A total of 460 serum samples were randomly collected from backyard chickens that had not been previously vaccinated against IBDV. The collected sera were examined using an enzyme-linked immunosorbent assay (ELISA). Data on epidemiological risk factors were collected through face-to-face interviews with owners and subjected to both uni- and multivariable risk analyses to determine their association with IBDV infection. Using ELISA, the overall seroprevalence of IBDV antibodies in backyard chickens was 83.4% (95% confidence interval: 79.8%–86.6%), among which, a significantly higher seroprevalence was recorded in females (83.4%, 345/350), 4–6 weeks age group (95.3%, 244/256), and unhealthy (95.0%, 57/60) backyard chickens than those of males, other age groups, and healthy chickens, respectively. Furthermore, chickens reared in free-ranging housing systems (93.3%, 280/300) and poor-conditioned houses (98.0%, 147/150) showed a significantly higher seropositivity of IBDV antibodies than those reared in separated housing systems and other hygienic-conditioned houses, respectively. Moreover, compared with their counterparts, a higher but nonsignificant seroprevalence of IBDV antibodies was observed in backyard chickens that were selected from Fulbaria Upazila (88.8%; 80/90) and which were brought from the marketplace (85.7%, 60/70). A higher seropositivity of IBDV antibodies was shown to be statistically associated with various critical epidemiological risk factors, indicating that field strains of IBDV were exposed in backyard chickens and could be readily transferred horizontally. Proper prevention and control methods, villagers' awareness of IBD, and the rapid and widespread use of seroepidemiological investigations could help to reduce the spread of IBDV infection in backyard chickens.